Anaerobic Digestion in Biogas Production from Organic Matter: A Bibliometric Analysis from 2000 to 2021 - Mizger-Ortega, Jesus; Vanegas Chamorro, Marley; Quintero, Miguel Celis (International Journal of Energy Economics and Policy, 2022)
This work describes the contribution of researchers worldwide in the field of the biogas production in the period 2000-2021. A bibliometric approach was applied to analyze scientific publications in the area using the Scopus Elsevier database. From 2000 to 2021, there were 1198 articles developed by 4212 authors from 2789 research institutions distributed in 96 countries. Scientific articles come mainly from China, Italy, and the United States. The most productive journals, authors, institutions, and countries are Bioresource Technology, Irini Angelidaki, Danmarks Tekniske Universitet, and China. All this research is of supreme importance for the development of this line of research at the Universidad del Atlántico, where research projects are currently being developed that will contribute to the strengthening of the national and international scientific community